2020
DOI: 10.3390/vaccines8030400
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Erythrocytic Vaccines against Malaria

Abstract: Malaria, caused by the protozoan Plasmodium, is a devastating disease with over 200 million new cases reported globally every year. Although immunization is arguably the best strategy to eliminate malaria, despite decades of research in this area we do not have an effective, clinically approved antimalarial vaccine. The current impetus in the field is to develop vaccines directed at the pre-erythrocytic developmental stages of Plasmodium, utilizing novel vaccination platforms. We here review the most promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 110 publications
1
18
0
Order By: Relevance
“…Despite numerous challenges, significant progress has been made toward the development of protective vaccines against preerythrocytic malaria infection. Many vaccine approaches have been evaluated in preclinical animal models, with few advancing into the clinic or beyond Phase 1 studies 70 . Encouraged by the successes of mRNA vaccines against other infectious diseases 17 , we applied an analogous approach to the age-old problem of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous challenges, significant progress has been made toward the development of protective vaccines against preerythrocytic malaria infection. Many vaccine approaches have been evaluated in preclinical animal models, with few advancing into the clinic or beyond Phase 1 studies 70 . Encouraged by the successes of mRNA vaccines against other infectious diseases 17 , we applied an analogous approach to the age-old problem of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, experimental results have confirmed that homologous or heterologous priming using viral vector approach could induce the CMI [71]. By using this approach, ME-TRAP, CSVAC (encodes PfCSP alongside a truncated C-terminal lacking 14 amino acids of CSP GPI anchor moiety), combination of PfTRAP with liver stage antigen 1 (LSA1) & LSA2 were developed and tested for their efficacy [42]. The enhanced T-cell based response is the major advantage of this approach.…”
Section: History Of Malaria Vaccine Developmentmentioning
confidence: 96%
“…Similarly, to target particularly the infected RBCs containing merozoites and preventing them to infect other RBCs in the blood/ symptomatic stage has been very difficult. Nonetheless, the longest exposure of infected sporozoites towards the host immune system by invading hepatocytes in the liver stage (5.5 to 7 days in humans and 48 hrs in rodents) and releasing of thousands of merozoites which further continue the blood-stage or symptomatic stage of infection makes the LS most promising stage for the target of vaccine development [14,42], though LS-vaccine has its own limitation of tedious and challenging task of sporozoites.…”
Section: Approach Of Vaccine Development: a Ray Of Hopementioning
confidence: 99%
See 1 more Smart Citation
“…While RAS provides protective immunity against homologous challenge, protection against heterologous challenge has proven problematic (24). In addition, the requirements for a cold chain to maintain the infective irradiated sporozoites and need for repeated immunizations pose significant obstacles to its wide-spread use (25,26). Both CSP and TRAP subunit-based vaccines (RTS,S and ME-TRAP, respectively) have successfully elicited sterile immunity against malaria infection in humans; however, both have demonstrated only modest efficacy (27).…”
Section: Introductionmentioning
confidence: 99%